Temporal trends of waitlistings for liver transplantation in Italy: The ECALITA (Evolution of IndiCAtion in LIver transplantation in ITAly) registry study. Issue 12 (December 2022) - Manzia, Tommaso Maria; Trapani, Silvia; Nardi, Alessandra; Ricci, Andrea; Lenci, Ilaria; Milana, Martina; Angelico, Roberta; De Feo, Tullia Maria; Agnes, Salvatore; Andorno, Enzo; Baccarani, Umberto; Carraro, Amedeo; et al.
Abstract: Background: Over the last decades relevant epidemiological changes of liver diseases have occurred, together with greatly improved treatment opportunities. Aim: To investigate how the indications for elective adult liver transplantation and the underlying disease etiologies have evolved in Italy. Methods: We recruited from the National Transplant Registry a cohort comprising 17, 317 adults patients waitlisted for primary liver transplantation from January-2004 to December-2020. Patients were divided into three Eras:1(2004–2011), 2(2012–2014) and 3(2015–2020). Results: Waitlistings for cirrhosis decreased from 65.9% in Era 1 to 46.1% in Era 3, while those for HCC increased from 28.7% to 48.7%. Comparing Eras 1 and 3, waitlistings for HCV-related cirrhosis decreased from 35.9% to 12.1%, yet those for HCV-related HCC increased from 8.5% to 26.7%. Waitlistings for HBV-related cirrhosis remained almost unchanged (13.2% and 12.4%), while those for HBV-related HCC increased from 4.0% to 11.6%. ALD-related cirrhosis decreased from 16.9% to 12.9% while ALD-related HCC increased from 1.9% to 3.9%. Conclusions: A sharp increase in liver transplant waitlisting for HCC and a concomitant decrease of waitlisting for cirrhosis have occurred In Italy. Despite HCV infection has noticeably decreased, still remains the primary etiology of waitlisting for HCC, while ALD and HBV represent the main causes for cirrhosis.